A Couple of Conjectures that Point to Hands in Sophocles - Taplin, Oliver (Hyperboreus, 2015)
The need to include stage-directions in a new translation of Sophocles has drawn attention to – predictably – the bow in Philoctetes, and – less predictably – to hands in Oedipus. This has led to the proposal of changing a simple article to a deictic indicator at Phil. 262 and OT 1022. These are offered not as emendations of the transmitted text but as plausible improvements which call for the addition of only one letter.